Can flavoprotein monooxygenases functionalize long-chain n-alkanes? - Raul Mireles; Arne Matthews; Robin Teufel; Lianet Noda-García (PLoS ONE, 2025)
Long-chain n-alkane functionalization is relevant for industrial and environmental applications, but it remains a significant challenge due to the inherent stability of their covalent bonds. Biocatalytic approaches offer promising strategies due to their potential for selective, efficient, and environmentally friendly processes. Among the enzyme families known to functionalize long-chain n-alkanes, one iron-binding protein, AlkB, has been characterized. Additionally, two distinct metal-free flavin-dependent enzymes, LadA and AlmA, are presumed to perform this function. Unlike the membrane-bound AlkB, LadA and AlmA are soluble proteins, making them more amenable to engineering and scalable industrial applications. In this study, we attempted to reproduce and optimize the n-alkane monooxygenase activity of LadA. We tested the functionality of this enzyme, an optimized variant, and four novel homologs under in vitro conditions. Despite extensive efforts, we were unable to detect any long-chain n-alkane hydroxylation. Analysis of LadA’s protein superfamily and the reported experimental evidence indicate that LadA may be involved in the metabolism of long-chain n-alkanes. However, its role in the first oxo-functionalization step could not be corroborated. Similar conclusions were published regarding AlmA’s activity. Altogether, these findings challenge the current understanding of flavoprotein monooxygenases as long-chain n-alkane monooxygenases and underscore the need for further investigation into their biochemical role.